2019
DOI: 10.1177/2378023119831801
|View full text |Cite
|
Sign up to set email alerts
|

Where’s the Beef? How Masculinity Exacerbates Gender Disparities in Health Behaviors

Abstract: Men in the United States have higher rates of life-threatening diseases than do women, in part due to behavioral differences in health practices. We argue that men's enactment of masculinity in their daily lives contributes to health behavior differences. We focus on meat consumption, a masculine-stereotyped dietary practice that epidemiological studies have linked to negative health outcomes. In study 1, nationally representative survey data indicate men report less healthy lifestyle preferences than do women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 39 publications
2
34
1
3
Order By: Relevance
“…However, we also found that being married was associated with higher likelihood of eating red meat almost every or every day. Couples' eating patterns are generally shared (Pachucki et al, 2011) and traditional gender roles around preparing and sharing meals may encourage married men and women to consume more meat (Nakagawa & Hart, 2019). Efforts to eat more healthfully may also be limited by a spouse's commitment to change.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also found that being married was associated with higher likelihood of eating red meat almost every or every day. Couples' eating patterns are generally shared (Pachucki et al, 2011) and traditional gender roles around preparing and sharing meals may encourage married men and women to consume more meat (Nakagawa & Hart, 2019). Efforts to eat more healthfully may also be limited by a spouse's commitment to change.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the extension of masculinity threat research to SC, men are less motivated to engage in SC when their masculinity is threatened, and more likely to engage when their masculinity is affirmed (Brough, Wilkie, Ma, Isaac, & Gal, ). For instance, men who experience masculinity threat are less likely to buy “green” products (Brough et al., ) and to favor meat‐eating (Nakagawa & Hart, ), which is culturally equated with masculinity (Greenebaum & Dexter, ). One explanation for these preferences may be that men anticipate greater discomfort when engaging in “feminine” pro‐environmental behaviors compared to women engaging in “masculine” behaviors (Johnson et al., ).…”
Section: Gendered Differences In Sc Behaviormentioning
confidence: 99%
“…In order to counter this feminine stigmatization, Rome argues that men purposefully chose to use science and economic terms to promote environmentalism during this time period, which continues to influence gender differences in SC solutions (as discussed later). Thus, it is possible that a legacy of concerns about the social consequences of gender role violations could affect the motivations and interests of women and men to engage in specific types of SC (Brough et al., ; Nakagawa & Hart, ; Swim, Vescio, Dahl, & Zawadzki, ).…”
Section: Gendered Differences In Sc Behaviormentioning
confidence: 99%
“…Researchers have suggested that it is timely and necessary to increase young adults' awareness about the environmental impact of meat consumption (Graham and Abrahamse, 2017). Whereas meat can be part of a healthy and sustainable diet (Willett et al, 2019), research indicates that an overconsumption of meat is detrimental for our environment (Walker et al, 2019) and our health (Nakagawa and Hart, 2019).…”
Section: Introductionmentioning
confidence: 99%